A Synergic Approach of Dredging Disposal and Extraction of Sand with Reference to Hugli Estuary (Global Journals of Research in Engineering, 2023)
The channel leading to the Haldia Dock Complex HDC create unpredicted flow field resulting nonlinear sediment transport over critical stretches during different season Thus the irregular sediment transport siltation and fall in navigable depth in the shipping channel remained permanent cause of worry Therefore maintenance dredging by Trailer Suction Hopper Dredgers TSHD is necessary In the context of dredging-disposal scenario an innovative synergic dredging disposal treatment plan has been conceptualized to reuse the dredged material by extracting sand through the plants installed on barges and thereafter transport it through waiting barges This paper deals with the methodology involved in the entire chain of events dredging by THSD disposal through barges-transport to installed sand washing plants over another big barge-extraction of sand-transfer to waiting barges-supply for industrial use in geotechnical engineering that justifies reuse of materials giving boost to other industry and increases The entire operation will be on the barge and this will be unique innovative concept applicable for Hugli estuary where the mode of shore disposal could not be taken up due to paucity of land and other occupational hazard This will also serve the purpose of shore disposal cum silt trap dredging aimed to reduce siltation and recirculation yielding decrease in annual dredging quantity in long run
Keywords: auckland bar; dredging disposal; haldia dock complex; hugli estuary; TSHD